Investigation of the Anti-Inflammatory Activity of Fusaproliferin Analogues Guided by Transcriptome Analysis - Kuang, Qi-Xuan; Lei, Li-Rong; Li, Qing-Zhou; Peng, Wan; Wang, Yu-Mei; Dai, Yi-Fei; Wang, Dong; Gu, Yu-Cheng; Deng, Yun; Guo, Da-Le (Frontiers in Pharmacology, 2022)
(1) Background: Excessive inflammation results in severe tissue damage as well as serious acute or chronic disorders, and extensive research has focused on finding new anti-inflammatory hit compounds with safety and efficacy profiles from natural products. As promising therapeutic entities for the treatment of inflammation-related diseases, fusaproliferin and its analogs have attracted great interest. However, the underlying anti-inflammatory mechanism is still poorly understood and deserves to be further investigated. (2) Methods: For the estimation of the anti-inflammatory activity of fusaproliferin (1) and its analogs (2-4) in vitro and in vivo, lipopolysaccharide (LPS)-induced RAW264.7 macrophages and zebrafish embryos were employed. Then, transcriptome analysis was applied to guide subsequent western blot analysis of critical proteins in related signaling pathways. Surface plasmon resonance assays (SPR) combined with molecular docking analyses were finally applied to evaluate the affinity interactions between 1-4 and TLR4 and provide a possible interpretation of the downregulation of related signaling pathways. (3) Results: 1-4 significantly attenuated the production of inflammatory messengers, including nitric oxide (NO), reactive oxygen species (ROS), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β), as well as nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), in LPS-induced RAW264.7 macrophages. Transcriptome analyses based on RNA-seq indicated the ability of compound 1 to reverse LPS stimulation and the nuclear factor kappa-B (NF-κB) and mitogen-activated protein kinase (MAPKs) signaling pathways contribute to the anti-inflammatory process. Experimental verification at the protein level revealed that 1 can inhibit the activation of IKK, degradation of IκBα, and phosphorylation of NF-κB and reduce nuclear translocation of NF-κB. 1 also decreased the phosphorylation of MAPKs, including p38, extracellular regulated protein kinases (ERK), and c-Jun N-terminal kinase (JNK). SPR assays and molecular docking results indicated that 1-4 exhibited affinity for the TLR4 protein with KD values of 23.5~29.3 μM. (4) Conclusions: Fusaproliferin and its analogs can be hit compounds for the treatment of inflammation-associated diseases.